One hundred twelve cases of 46, XY DSD patients after initial gender assignment: a short-term survey of gender role and gender dysphoria - Liping Hou; Ming Zhao; Lijun Fan; Bingyan Cao; Jiajia Chen; Yonghua Cui; Michel Polak; Chunxiu Gong (Orphanet Journal of Rare Diseases, 2021)
Abstract Background 46, XY disorders of sex development (46, XY DSD) are congenital disorders with 46, XY chromosomal karyotype but inconsistent gonadal/phenotypic sex. One of the biggest concerns for parents and clinicians is the gender assignment. However, there is no standard uniform of care nor consensus at present. We sought to evaluate the current treatment's rationality and provide a reference basis for the gender reassignment in 46, XY DSD patients with a specific diagnosis. Methods We conducted a cross-sectional survey of gender role with the Pre-school Activities Inventory (PSAI), the Children's Sex Role Inventory (CSRI) in 46, XY DSD patients and set up control groups comparison. Psychiatrist assessed gender dysphoria in patients ≥ 8-year-old with the criteria of diagnostic and statistical manual of mental disorders, 5th edition (DSM-5). Results A total of 112 responders of 136 patients participated in this study (82.4%, aged 2–17.8 years, median age: 4-year-old). The follow-up period was from 6 months to 10 years (median: 2 years). Twenty-five females were reassigned to the male gender after a specific diagnosis (16/25 (64%) in 5 alfa-reductase-2 deficiency (5α-RD2), 5/25 (20%) in partial androgen insensitivity syndrome (PAIS), 4/25 (16%) in NR5A1gene mutation). Male gender assignment increased from 55.3 (n = 62) to 77.7% (n = 87). The median PSAI score was similar to the control males in 5α-RD2, PAIS, and NR5A1 gene mutation groups (p > 0.05); while identical to the control females in complete androgen insensitivity syndrome (CAIS) and CYP17A1 gene mutation groups (p > 0.05). PSAI score of children raised as male was higher than those of CAIS and CYP17A1 groups raised as female (p < 0.05). CSRI scale showed no statistical differences in the consistency of gender roles and reassigned gender between 46, XY DSD patients and control groups (p > 0.05). None of the patients over 8-year-old (n = 44) had gender dysphoria. Conclusion The reassigned gender in 46, XY DSD patients is consistent with their gender role during early childhood. None of them had gender dysphoria. The molecular diagnosis, gonadal function, and the gender reassignment are congruent within our Chinese cohort. Long-term follow-up and more evaluation are still required.